Effect of silver nanoparticles, synthesized from fleshy stem and leaves extract of Brassica campestris L., on Alternari lini inhibition - Shah, Syed Awais Hussain (Journal of Agriculture and Applied Biology, 2020)
Several fungal pathogens showed resistance against pesticides, plant mediated synthesized silver nanoparticles have been recognized as effective against them. The present research work was an attempt to synthesize silver nanoparticles by using fleshy stem and leaves ex-tract of Brassica compestris L. from silver nitrate, which reduces it to synthesized silver nanoparticles. Biosynthesized AgNP’s were char-acterized by different techniques like UV-visible spectrophotometry and Field Emission Scanning Electron Microscopy and fungal inhibi-tory activity by well diffusion method. The colour change of solution indicated the synthesis of silver nanoparticles. UV-visible spectro-photometer showed the peak between 415 to 455 nm for fleshy stem and leaves extract of B. compestris and Field Emission Scanning Elec-tron Microscope analysis revealed that spherical shaped nanoparti-cles with size 20-65 nm. These synthesized nanoparticles showed in-hibitory activity against fungi, Alternaria lini, a linseed blight patho-gen which causes linseed blight disease in Linum usitatissimum L. The 30 μl concentrations of silver nanoparticles had showed significant inhibition to growth of A. lini. These findings may suggest AgNP’s syn-thesized by B. compestris used against plant pathogenic fungi.